Jefferson Rebuffed: The United States And The future Of Internet Governance - Mayer-Schönberger, Vikor; Ziewitz, Malte (Science and Technology Law Review, 2007)
When the World Summit on the Information Society (WSIS) concluded in Tunis in November 2005, it was hailed as a great achievement. There is, however, another yet untold story about the WSIS negotiations and the subsequent outcome. It focuses on the ill-fated European proposal to internationalize Internet governance and to curtail the policy-making power of the Internet Corporation for Assigned Names and Numbers (ICANN), the corporation currently in charge of Internet naming and numbering. It is the story of a missed opportunity for what could have become a “constitutional moment” in international Internet governance. With its Constitution arguably being the oldest and most enduring worldwide, the United States traditionally has been at the forefront of fostering and advancing constitutional governance structures, at times even through the use of force. Why then, has the United States vigorously opposed the European proposal, with its concept of self-constrained governance in the important context of global information flows? The aim of this article is to offer an answer.